Taiwan and Chinese nationalism : national identity and status in international society - Hughes, Christopher W. (Politics in Asia series., 1997)
This study examines the problems which will inevitably arise as a result of China's claims on Taiwan, and analyses Taiwan's 'post-nationalist' identity.